Experience of transfer from child to adult mental health services of young people with autism spectrum disorder. Issue 4 (July 2020) - Merrick, Hannah; King, Chris; McConachie, Helen; Parr, Jeremy R.; Le Couteur, Ann
Abstract : Background: Transition from child-centred to adult mental health services has been reported as challenging for young people. It can be especially difficult for young people with autism spectrum disorder (ASD) as they manage the challenges of adolescence and navigate leaving child and adolescent mental health services (CAMHS). Aims: This study examines the predictors of transfer to adult mental health services, and using a qualitative analysis, explores the young people's experiences of transition. Method: A UK sample of 118 young people aged 14–21 years, with ASD and additional mental health problems, recruited from four National Health Service trusts were followed up every 12 months over 3 years, as they were discharged from CAMHS. Measures of mental health and rich additional contextual information (clinical, family, social, educational) were used to capture their experiences. Regression and framework analyses were used. Results: Regression analysis showed having an attention-deficit hyperactivity disorder diagnosis and taking medication were predictors of transfer from child to adult mental health services. Several features of young people's transition experience were found to be associated with positive outcomes and ongoing problems, including family factors, education transitions and levels of engagement with services. Conclusions: The findings show the importance of monitoring and identifying those young people that might be particularly at risk of negative outcomes and crisis presentations. Although some young people were able to successfully manage their mental health following discharge from CAMHS, others reported levels of unmet need and negative experiences of transition.